Most programmers probably already know this, but I have observed that for beginner programmers, it is quite frequently unknown or overlooked.
When you evaluate expressions you need not evaluate "If <expression> = true then", you simply evaluate "If <expression> then"
This is because <expression> already produces a Boolean value, and an if then branch breaks down to the following logic:
'True was the case
'False was the
So when you evaluate the following expression for example:
(1+2 = 4)
This will automatically become false, because 1+2 does not equal 4.
True will always = true (It is what it is!)
False will always = false(It is what it is!)
Which means that saying:
(1+2=4) = true then
is effectively saying the same as saying
> = true then
'False was the case
Bus since a Boolean "is what is", we need not check if "<Boolean>" = true...
So the following is the same as above:
And the following is just as absurd as evaluating true in an expression:
(((((1 + 2) = 3) =
In conclusion, try to remember, "It is what it is."